Program Bimbingan Belajar Gratis Bahasa Indonesia, Matematika, IPS, dan Bahasa Inggris di SD Negeri 035950 Silencer - Usman Sidabutar; Hana Grace Hutagalung; Desi Sastria Lumban gaol; Dian Nopitasari Purba; Sandly D Sihotang; Irene Anjeli Purba (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Tutorial Learning in education is a part of creativity to increase an innovative and adaptive in learning systems by which the curriculum applied through the teaching learning process. In concerned to global demand as the digital base of manner in academics, the students and lecturers of the Faculty of Teacher Training, University of HKBP Nommen Medan carried out Pengabdian Kepada Masyarakat (PKM) entitled